2007
DOI: 10.1007/s00213-007-0929-2
|View full text |Cite
|
Sign up to set email alerts
|

Neurobehavioral protection by single dose l-deprenyl against MPTP-induced parkinsonism in common marmosets

Abstract: The present preclinical methods using continuous recording of activity of marmosets in their living cages and autoradiography using dopamine transporter ligand might be sensitive for detecting protective actions of drugs for Parkinson's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 22 publications
(30 reference statements)
3
25
0
Order By: Relevance
“…The common marmoset ( Callithrix jacchus ) is an increasingly popular NHP species for developing models of neurological disorders (‘t Hart et al, 2000; Okano, Hikishima, Iriki, & Sasaki, 2012; Tardif, Abee, & Mansfield, 2011). Conditions such as Parkinson’s disease (Ando et al, 2008; Ando et al, 2012; Gnanalingham, Smith, Hunter, Jenner, & Marsden, 1993; Huot et al, 2012), Huntington’s disease (Kendall et al, 1998; Maclean, Baker, Ridley, & Mori, 2000), Alzheimer’s disease (Baker, Ridley, Duchen, Crow, & Bruton, 1993) and multiple sclerosis (‘t Hart et al, 2000; Genain & Hauser, 1997) have been modeled in marmosets mainly by neurotoxin administration. Advances in the role of genetics in these disorders, as well as in the tools to generate transgenic and genomic edited models, are moving the field towards a new generation of disease models.…”
Section: Introductionmentioning
confidence: 99%
“…The common marmoset ( Callithrix jacchus ) is an increasingly popular NHP species for developing models of neurological disorders (‘t Hart et al, 2000; Okano, Hikishima, Iriki, & Sasaki, 2012; Tardif, Abee, & Mansfield, 2011). Conditions such as Parkinson’s disease (Ando et al, 2008; Ando et al, 2012; Gnanalingham, Smith, Hunter, Jenner, & Marsden, 1993; Huot et al, 2012), Huntington’s disease (Kendall et al, 1998; Maclean, Baker, Ridley, & Mori, 2000), Alzheimer’s disease (Baker, Ridley, Duchen, Crow, & Bruton, 1993) and multiple sclerosis (‘t Hart et al, 2000; Genain & Hauser, 1997) have been modeled in marmosets mainly by neurotoxin administration. Advances in the role of genetics in these disorders, as well as in the tools to generate transgenic and genomic edited models, are moving the field towards a new generation of disease models.…”
Section: Introductionmentioning
confidence: 99%
“…Our success with deriving transgenic Callithrix embryonic stem cell clones allows the use of these reporter cell lines to follow and track transplanted cells in preclinical studies. Furthermore, targeted gene knockdown could be developed using overexpression or short hairpin RNA interference (shRNAi) vectors [20] to study human diseases involving the loss of function of specific genes in nonhuman primates, including Huntington's disease [21], spinal cord injury [22], and Parkinson's disease [23]. …”
Section: Discussionmentioning
confidence: 99%
“…The behavioral characteristics of marmosets in the framework of preclinical PD studies have been described in previous studies [19]. In more detail, normal marmosets in individual living cages move freely, leap between mesh cage walls, and cling to the walls in the daytime, and are sedentary at night.…”
Section: Introductionmentioning
confidence: 97%
“…Thus, MPTP is often used to establish PD model in various primate species, including baboons [12], macaques [6], [13], velvet monkeys [14], squirrel monkeys [7], [15] and common marmosets [16], [17], [18], for studying the pathophysiology, etiology, pathogenesis, and possible treatment options for PD. Preclinical (non-clinical) studies have shown that the common marmoset is a suitable model for not only the identification of effective pharmacological treatments but also the evaluation of neuroprotective therapies [19], [20], [21], [22], [23].…”
Section: Introductionmentioning
confidence: 99%